The impact of Google Docs on student collaboration: A UAE case study. (December 2015) - Ishtaiwa, Fawzi Fayez; Aburezeq, Ibtehal Mahmoud
Abstract: This study had a two-fold aim; (i) to investigate the impact of Google Docs on enhancing four types of collaboration, and (ii) to identify the factors limiting student collaboration via Google Docs. Data collected through questionnaires and semi-structured interviews. The findings revealed that Google Docs is a valuable application to promote student–student and student–instructor interactions. In addition, it was found that Google Docs has the power to improve student–content and student–interface interactions through the resources and features offered by the application. Finally, the findings revealed a number of factors limiting the use of Google Docs for collaborative purposes. Highlights: Google Docs promotes student–student and student–instructor interactions. Google Docs resources and features are useful to facilitate collaborative learning. There are a number of factors limiting the use of Google Docs for collaboration.